3D Bioprinted Chitosan-Based Hydrogel Scaffolds in Tissue Engineering and Localised Drug Delivery - Maria Lazaridou; Dimitrios N. Bikiaris; Dimitrios A. Lamprou (MDPI AG, 2022)
Bioprinting is an emerging technology with various applications in developing functional tissue constructs for the replacement of harmed or damaged tissues and simultaneously controlled drug delivery systems (DDSs) for the administration of several active substances, such as growth factors, proteins, and drug molecules. It is a novel approach that provides high reproducibility and precise control over the fabricated constructs in an automated way. An ideal bioink should possess proper mechanical, rheological, and biological properties essential to ensure proper function. Chitosan is a promising natural-derived polysaccharide to be used as ink because of its attractive properties, such as biodegradability, biocompatibility, low cost, and non-immunogenicity. This review focuses on 3D bioprinting technology for the preparation of chitosan-based hydrogel scaffolds for the regeneration of tissues delivering either cells or active substances to promote restoration.